The longitudinal association between potential stressful life events and the risk of psychosocial problems in 3-year-old children - van Grieken, Amy; Luo, Jie; Horrevorts, Esther M. B.; Mieloo, Cathelijne L.; Kruizinga, Ingrid; Bannink, Rienke; Raat, Hein (Frontiers in Public Health, 2023)
Background Experiencing certain potentially stressful life events can impact psychosocial well-being among school-aged children and adolescents. This study aims to evaluate the association between life events occurring before age 2 and risk of psychosocial problems at 3 years of age. Methods All parents invited for the regular well-child visit when their child was 2 years of age by the preventive Youth Health Care in the Rotterdam-Rijnmond area, the Netherlands, were invited to participate in this study. In total 2,305 parents completed the baseline questionnaire at child age 2-years; 1,540 parents completed the questionnaire at child age 3-years. The baseline questionnaire included a life events assessment (12 items), and tension caused by the event (range 0–3). At child age 3-years the questionnaire included the Strengths and Difficulties Questionnaire (SDQ) to assess risk of psychosocial problems. Logistic regression models were applied. Results In the current study 48.5% of families experienced ≥1 life event before child age 2 years. Divorce and problems in the relationship between the parents received the highest perceived severity score [respectively 2.1 (SD = 0.8) and 2.0 (SD = 0.7)]. Children experiencing ≥1 event before the age of 2 years were at higher risk of psychosocial problems at 3 years of age, compared to children that had experienced no life event (1–2 events OR = 1.50, 95%CI: 1.09; 2.06, and >2 events OR = 2.55, 95%CI 1.64; 4.00, respectively). When life events caused high perceived levels of tension, there was also an association with an increased risk of psychosocial problems at age 3-years (OR = 2.03, 95%CI 1.43; 2.88). Conclusions Approximately half of children in our study experienced a potential stressful life event before the age of 2 years. Results suggest an association between experiencing a life event and risk of psychosocial problems at child age 3-years. These findings emphasize the need for child health care professionals to pay attention to life events taking place in the life of young children in order to provide appropriate support.